Anti‐ictogenic and antiepileptogenic properties of perampanel in mature and immature rats. (29th August 2017) - Dupuis, Nina; Enderlin, Julie; Thomas, Jeremy; Desnous, Béatrice; Dournaud, Pascal; Allorge, Delphine; Auvin, Stéphane
Summary: Objective: Perampanel (PER) is a selective noncompetitive antagonist at α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors, the first of its class approved for the adjunctive treatment of partial onset seizures and generalized seizures. This study explored anti‐ictogenic and antiepileptogenic effects of PER in rats at different stages of development. Methods: Using a rapid kindling model in postnatal day 14 (P14), P21, P28, and P60 rats, we studied two doses of PER: 1 and 2 mg/kg injected intraperitoneally 30 min before afterdischarge assessment. We also assessed blood and brain concentrations of PER 30 min after the injection. Results: PER 2 mg/kg significantly increased the afterdischarge threshold (ADT) at all ages, whereas PER at 1 mg/kg increased ADT only in P21 rats. PER 2 mg/kg also shortened the afterdischarge duration in P14 and P28 rats. PER increased the number of stimulations required to achieve a stage 4–5 seizure in a dose‐dependent manner in P14 and P21 rats, with almost complete elimination of stage 4–5 seizures. At P28, only PER 2 mg/kg increased the number of stimulations required to develop a stage 4–5 seizure. In contrast, PER had no effect on the number of stage 4–5 seizures at P60. We did not observed any age‐dependent significant difference in the serum and brain levels of PER 30 min after the injection. Significance: PER exerted anti‐ictogenic effects from P14 to P60 independent of brain maturation. PER also exhibited antiepileptogenic effects with a stronger effect in the younger animals.